2016
DOI: 10.1007/s11881-016-0121-7
|View full text |Cite
|
Sign up to set email alerts
|

Implicit learning deficits among adults with developmental dyslexia

Abstract: The aim of the present study was to investigate implicit learning processes among adults with developmental dyslexia (DD) using a visual linguistic artificial grammar learning (AGL) task. Specifically, it was designed to explore whether the intact learning reported in previous studies would also occur under conditions including minimal training and instructions that do not reveal the grammatical nature of the strings. Twenty-nine (14 DD and 15 typical development (TD)) adults were presented with letter sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 60 publications
1
35
1
2
Order By: Relevance
“…Namely, individuals with DD as well as TD readers did not exhibit improvement in performance when given explicit information about the statistical nature of the stimuli. This finding is in contrast to the improvement reported in the previous visual AGL study using explicit visual task (Kahta & Schiff, ). The contrasting findings of the two studies suggest that the ability of adults with DD to explicitly compensate for deficits in SL is limited by the modality of the stimuli.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Namely, individuals with DD as well as TD readers did not exhibit improvement in performance when given explicit information about the statistical nature of the stimuli. This finding is in contrast to the improvement reported in the previous visual AGL study using explicit visual task (Kahta & Schiff, ). The contrasting findings of the two studies suggest that the ability of adults with DD to explicitly compensate for deficits in SL is limited by the modality of the stimuli.…”
Section: Discussioncontrasting
confidence: 99%
“…The aim of the current study was to examine SL processes among adults with DD using A‐AGL. Like the results of the visual AGL task (Kahta & Schiff, ), the results of the current study indicated that individuals with DD are able to extract the underlying regularities of a complex auditory stimuli with less efficiency than the TD counterparts. In addition, performance on the implicit A‐AGL was correlated with reading performance, that is, decoding, accuracy, and fluency.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results suggest that paired-associated learning is impaired when it requires learning of a novel sequence of speech sounds – which taxes the procedural system – but that learning of arbitrary associations, which employs declarative learning, is intact. Further evidence that declarative memory is unimpaired comes from a study reporting that, when an implicit AGL task is made explicit, learning differences are no longer seen in a group of adults with dyslexia [28].…”
Section: Specificity Of Learning Difficulties In Developmental Languamentioning
confidence: 99%
“…Incidental statistical learning is considered to be a domain-general and implicit learning process innate to humans, regardless of learner's ages [1,2], suggesting that we might constantly and unconsciously perform statistical learning of sequential stimuli such as language and music [34,35]. Some researchers reported that dyslexia is difficult to perform statistical learning compared to healthy learners [36,37]. Improvement in physical fitness might be useful as clinical application for rehabilitation of language learning in dyslexia.…”
Section: Discussionmentioning
confidence: 99%